Geographies of developing areas : the global south in a changing world - Williams, Glyn (Routledge, 2014)
"Geographies of Developing Areas is thought provoking and accessible introductory text, presenting a fresh view of the Global South that challenges students' pre-conceptions and promotes lively debate. Rather than presenting the Global South as a set of problems, from rapid urbanization to poverty, this book focuses on the diversity of life in the South, and looks at the role the South plays in shaping and responding to current global change. The core contents of the book integrate 'traditional' concerns of development geographers, such as economic development and social inequality, with aspects of the global South that are usually given less attention, such as cultural identity and political conflict. This edition has been fully updated to reflect recent changes in the field and highlight issues of security, risk and violence; environmental sustainability and climate change; and the impact of ICT on patterns of North-South and South-South exchange. It also challenges students to think about how space is important in both the directions and the outcomes of change in the Global South, emphasizing the inherently spatial nature of political, economic and socio-cultural processes. Students are introduced to the Global South via contemporary debates in development and current research in cultural, economic and political geographies of developing areas. The textbook consider how images of the so-called 'Third World' are powerful, but problematic. It explores the economic, political and cultural processes shaping the South at the global scale and the impact that these have on people's lives and identities. Finally, the text considers the possibilities and limitations of different development strategies.The main arguments of the book are richly illustrated through case study material drawn from across the Global South as well as full colour figures and photos. Students are supported throughout with clear examples, explanations of key terms, ideas and debates, and introductions to the wider literature and relevant websites in the field. The pedagogical features of the book have been further developed through discussion questions and activities that provide focused tasks for students' research, including investigation based around the book's case studies, and in-depth exploration of debates and concepts it introduces. "--